2005
DOI: 10.1002/jbm.b.30497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applied voltages on hydroxyapatite coating of titanium by electrophoretic deposition

Abstract: Hydroxyapatite (HA) coatings were deposited on titanium substrates by electrophoretic deposition (EPD) at constant voltage and dynamic voltage, respectively. Various surface morphologies were observed under different type of voltages. Under a constant voltage of 20 V, a dense HA coating could be prepared. Under a constant voltage of 200 V, big HA particles were deposited and the coating was porous. Under a dynamic voltage, a continuous gradient HA coating could be obtained. HA coatings were characterized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 49 publications
(52 reference statements)
1
40
0
Order By: Relevance
“…Increasing the electric field resulted in increased rate of deposition, but the deposited particles had shorter time to rearrange and therefore these coatings had a more porous microstructure 30) . Previously, we reported that HA coatings prepared at dynamic voltages consisted of particles with continuous gradient, and that the morphology was distinctly different from that prepared at a constant voltage 19) . However, the dynamic process and deposition mechanism were not discussed clearly.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Increasing the electric field resulted in increased rate of deposition, but the deposited particles had shorter time to rearrange and therefore these coatings had a more porous microstructure 30) . Previously, we reported that HA coatings prepared at dynamic voltages consisted of particles with continuous gradient, and that the morphology was distinctly different from that prepared at a constant voltage 19) . However, the dynamic process and deposition mechanism were not discussed clearly.…”
Section: Introductionmentioning
confidence: 88%
“…While bone compatibility is provided by the HA coating, the underlying metal possesses good ductility and strength. Deposition of HA coatings has been achieved by a number of methods, including plasma spraying [5][6][7] , ion implantation 8,9) , sputtering [10][11][12] , sol-gel coating [13][14][15] , biomimetic methods [16][17][18] , and electrophoretic deposition (EPD) [19][20][21] . Among these methods, EPD is a fairly rapid and inexpensive way of producing a dense and uniform coating on substrates even with complex geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The films were investigated for the development of hip prosthesis. Polyvinyl alcohol and N, N-dimethylformamide have also been added to HA suspensions to improve the adherence and strength of the coatings and to avoid cracking of the deposits upon drying (Meng et al 2006). However, it should be noted that the selection of dispersants, binders and other additives for biomedical applications is limited because some additives are toxic or may have adverse effects in contact with living tissue.…”
Section: Epd Of Hamentioning
confidence: 99%
“…Methods for manufacturing bioactive material coatings with chemical modifications include plasma spraying 27) , electrophoretic deposition 28) , and sputtering technique 29) . The plasma spray technique has been used to rapidly solidify aluminum oxide coatings on metal substrates 30) .…”
Section: Discussionmentioning
confidence: 99%